DESKRIPSI KESALAHAN BERBAHASA PADA TEKS KARANGAN SISWA KELAS IV - Hidayati, Urai Nur; Suparjan, Suparjan; Pranata, Rio (Universitas Tanjungpura, 2023)
The problem of this research is what are the errors in the use of capital letters in writing essays of students and what are the spelling errors found in the use of full stop and comma punctuation in writing essays. The purpose of this research is to describe: 1) errors in writing capital letters; 2) spelling errors using periods and punctuation marks in the essays of grade IV students at SD Negeri 26 Pontianak Tenggara. This research is a qualitative research using descriptive research methods with data sources written by 32 students of class IV-A SDN 26 Pontianak Tenggara. The instrument in the research is a human instrument, namely researchers who act as instruments. Data collection techniques with documentation studies and reading recording techniques. The data analysis technique used is the Miles and Huberman model technique. The results of this study were 138 capital letter errors with a percentage of 51%, 63 dot errors with a percentage of 23%, and 69 comma errors with a percentage of 26%.